The Mistletoe Inn - Evans, Richard Paul (New York : Simon & Schuster, 2015)
"The New York Times bestselling "King of Christmas Fiction" presents a romantic new holiday story about two romance writers who are searching for the kind of love that, so far, they have only written about"--
Keywords: Christmas stories; Man-woman relationships -- Fiction; FICTION / Family Life; FICTION / Christian / General; Christmas stories; Romance fiction